Digestibility index marker type, but not inclusion level affects apparent digestibility of energy and nitrogen and marker recovery in growing pigs regardless of added oat bran1. (24th April 2018) - Wang, Tingting; Adeola, Olayiwola
Abstract: This study was conducted to investigate whether the apparent ileal digestibility (AID) of GE or nitrogen (N) was influenced by inclusion level and type of digestibility index marker (DIM) and inclusion level of oat bran (OB) and whether the apparent total tract digestibility (ATTD) of GE or DIM recovery was influenced by the 3 aforementioned factors and duration of feces collection. Six diets were formulated as a 2 × 3 factorial arrangement with 2 levels of OB (0 or 100 g/kg) and 3 levels of DIM (2.5, 5.0, or 7.5 g/kg). Chromic oxide and titanium dioxide were used as DIM. Both chromic oxide and titanium dioxide were added to the same diet, and their inclusion levels were consistent in each experimental diet. In Exp. 1, 18 barrows fitted with T-cannulas at the distal ileum were used in a triplicate 6 × 2 incomplete Latin Square design with 6 dietary treatments and 2 periods. The ileal digesta were collected for 3 d after 5-d adaptation, and the AID of GE and N were determined by measuring Cr or Ti in diets and ileal digesta samples. In Exp. 2, a total of 72 barrows were used in a randomized complete block design, and the feces were collected for either 3 or 5 d after a 7-d adaptation according to the assignment. Experimental diets were same as Exp. 1. The ATTD of GE was determined by both total collection and index methods, and DIM recovery was determined by measuring Cr or Ti. In Exp. 1, there was no interaction among OB level, DIM level, and DIM type for AID of GE and N. The AID of GE and N determined by Ti were greater ( P < 0.05) than Cr regardless of the OB level or DIM level. Neither the OB level nor the DIM level affected the AID of GE or N. In Exp. 2, no interaction among OB level, DIM level, duration of feces collection, and DIM type for ATTD of GE and DIM recovery was observed. The DIM level and duration of feces collection had no effect on ATTD of GE and DIM recovery. The total collection method resulted in greater ( P < 0.05) ATTD of GE than Ti, which was greater ( P < 0.05) than that determined by Cr. Similarly, the recovery of Ti was greater ( P = 0.007) than Cr. Inclusion of 100 g/kg OB decreased ( P = 0.003) ATTD of GE but did not affect the recovery of DIM. In conclusion, the AID of GE and N, the ATTD of GE, and the recovery of Cr or Ti were affected by DIM type, but not DIM level; the inclusion of OB had no effect on AID of GE and N, and DIM recovery; and the duration of feces collection had no effect on ATTD of GE and DIM recovery.